Factors that cause second language anxiety in speaking among form four students and ways to reduce them / Syazza ‘Atrah Abu Bakar - Abu Bakar, Syazza ‘Atrah (2011)
This research was conducted to analyze the causes of anxiety of Form Four students of SMK Bandar Baru Uda, Johor Bahru. A total of 30 students and 10 teachers were involved as respondents of the research. Students’ language anxiety was measured using a previous research done Tanveer (2008) questionnaire The research findings showed that most of the students experienced a great deal of anxiety when they used the target language inside as well as outside of the classroom. From the two subscales of communication apprehension and fear of negative evaluation, it is known that the causes of students’ anxiety were among all derived from negative self perceptions, fear of peer, language teacher’s as well as public’s evaluations and the fear of making mistakes in using the language. It was also found that there are various ways suggested by students and teachers in controlling and reducing the second language anxiety among the ESL learners.